2015
DOI: 10.1097/rlu.0000000000000854
|View full text |Cite
|
Sign up to set email alerts
|

68Ga DOTATATE PET/CT is an Accurate Imaging Modality in the Detection of Culprit Tumors Causing Osteomalacia

Abstract: (68)Ga DOTATATE PET/CT scan is an accurate imaging modality in the detection of tumors causing TIO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 29 publications
0
66
0
1
Order By: Relevance
“…No additional records were found screening the references of these articles, whereas six articles were excluded after the analysis of the full text. Therefore, 14 articles were included in the qualitative analysis (systematic review) [16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Three articles were excluded from the meta-analysis for possible patient data overlap [18,25,26].…”
Section: Literature Searchmentioning
confidence: 99%
“…No additional records were found screening the references of these articles, whereas six articles were excluded after the analysis of the full text. Therefore, 14 articles were included in the qualitative analysis (systematic review) [16][17][18][19][20][21][22][23][24][25][26][27][28][29]. Three articles were excluded from the meta-analysis for possible patient data overlap [18,25,26].…”
Section: Literature Searchmentioning
confidence: 99%
“…E PET/CT imaging had a sensitivity of 100% (32/32) and a specificity of 90.9% (10/11) with overall accuracy of 97.7% in the detection of tumours responsible for osteomalacia. 26 However, in this large study, the lesions were identified clearly on imaging. In our experience with 68 Ga-DOTANOC PET/CT, we were able to find multiple lesions.…”
Section: Discussionmentioning
confidence: 56%
“…However, the data available in the literature with the SSTR PET/CT-based imaging in these tumours are limited ( Table 2). [18][19][20][21][22][23][24][25][26] Among the variety of somatostatin analogues, most commonly used for imaging are 68 Ga-DOTA 0 -Ty 3 octreotate (DOTATATE), 68 Ga-DOTA 0 -Ty 3 octreotide (DOTATOC) and 68 Ga-DOTA 0 -NaI 3 octreotide (DOTANOC) with variable SSTR subtype specificity. The specific modification of octreotide at Position 3 in 68 Ga-DOTANOC leads to higher affinity to SSTR-2 and SSTR-5.…”
Section: Discussionmentioning
confidence: 99%
“…[15,16] 18 F-FDG PET/CT, 99m Tc-OCT scintigraphy, and 68 Ga DOTATATE PET/CT played a considerable role in revealing TIO-associated tumors. [1719] For these patients with TIO, complete surgical resection of causative tumors is the definitive treatment.…”
Section: Discussionmentioning
confidence: 99%